Visible-light-absorbing mesoporous TiO2 modified with tungstosilicic acid as photocatalyst in the photodegradation of 4-chlorophenol - Rengifo Herrera, Julian Andres (2014)
Visible-light-absorbing materials based on TiO2 modified with tungstosilicic acid (TSA; H4SiW12O40) were prepared using titanium isopropoxide as precursor and urea as a low-cost pore-forming agent. X-ray diffraction (XRD) measurements show evidence about the presence of anatase TiO2 in all samples and shifting of the anatase–rutile transition temperature toward temperatures higher than 600 °C. The FT-IR and FT-Raman studies showed that the main heteropolyoxometallate species present in the composites annealed up to 500 °C is the [SiW12O40]4− anion, which exhibited a strong interaction with TiO2 surface probably due to the formation of TSA–TiO2 complexes that should be responsible for its visible light absorption. The photocatalytic activity of these materials was tested using 4-chlorophenol as model pollutant. Results revealed that photocatalytic activity mainly depends on the TSA amount and the annealing temperature. The amount of degraded 4-CP increased with the increment of TSA content, with the one calcined at 600 °C being more active. Finally, it was found that these photocatalysts can be reused at least three times without an important decrease in the degradation and mineralization degrees.